Malaysian women’s state of well-being: Empirical validation of a conceptual model - Noor, Noraini M. (Routledge (bought from Heldref Publication in 2009), 2006)

(untitled)
The author carried out the present study to examine the determinants of Malaysian women’s well-being. Specifically, the author proposed a theoretical model of women’s roles and well-being—made up of roles, negative affectivity, conflict, and health—and statistically validated it in a group of women occupying both work and family roles (N = 389). Using a life-course approach (P. Moen, 1998) to roles and well-being, the author further examined the model in women of 3 different age groups (age of Group 1 = 20–29 years, age of Group 2 = 30–39 years, and age of Group 3 = 40 years and older). The results supported the proposed model, which showed reasonable fit when applied to the 3 groups of women. The results also indicated that the predictors of women’s wellbeing differ according to their respective age groups. The author discussed these findings in relation to the life-course approach to women’s roles.